Post a New Question

math

posted by .

solve the system by elimination.
6x-6y-4z=-10
-5z+4y-z=-12
2x+3y-2z=9

  • math -

    Multiply the last equation (both sides) by 2. That gives you
    4x + 6y - 4z = 18
    Add that to
    6x - 6y - 4z = -10
    That gives you
    10x -8z = 8
    So far, we have eliminated the variable y.
    Use similar tricks to get rid of x or z.

    I believe your second equation is typed incorrectly. Did you mean
    -5x +4y -z = -12?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question